Combination of SIRT1 and Src overexpression suggests poor prognosis in luminal breast cancer - Tan, Jie (Onco Targets Ther, 2018)
OBJECTIVES: 1) Analyze the correlation of SIRT1 and Src with human breast cancer (BC) prognosis; 2) explore the roles of SIRT1 and Src in BC cell proliferation, tumor invasion, and metastasis; and 3) analyze the correlation and interaction between SIRT1 and Src. MATERIALS AND METHODS: 1) Tissue microarray was used to analyze the expression of SIRT1 and Src in human BC tissues and the correlation between protein expression and cancer prognosis; 2) CCK8 assay was used to determine the influence of SIRT1 and Src inhibitors on BC cell proliferation; 3) Transwell migration assay and wound healing assay were used to determine the effect of SIRT1 and Src inhibitors on BC cell migration and invasion; and 4) Western blotting was used to analyze the correlation and interaction between SIRT1 and Src. RESULTS: 1) Combination of SIRT1 and/or Src positivity is a prognosis factor in BC, especially in luminal type; 2) MCF-7 cell proliferation is suppressed by SIRT1 inhibitor Ex527, and cell migration and invasion were inhibited by Src inhibitor bosutinib; 3) combined with Ex527, bosutinib has a significantly increased effect on MCF-7 cell migration suppression; and 4) there is a positive association between SIRT1 and Src both in BC tissues and in MCF-7 cells. CONCLUSION: 1) SIRT1 and Src overexpression are both correlated with poor prognosis in human BC; 2) SIRT1 + Src (SIRT1 and/or Src positivity) is a fine prognosis model for luminal-type BC; 3) SIRT1 is a copromotor of Src in BC migration and invasion, but not in cell proliferation; and 4) our results suggest a potential interaction or a common regulation pathway between SIRT1 and Src expression and activity.